Cerebral Toxoplasmosis: A Case Report with Correlation of Radiographic Imaging, Surgical Pathology, and Autopsy Findings. Issue 3 (September 2017) - Harrison, William T.; Hulette, Christine
Cerebral toxoplasmosis is an opportunistic infection of the central nervous system. Certain radiographic findings can be highly suggestive of the disease, but there is considerable overlap with both lymphoma and brain metastases, making the diagnosis difficult or delayed. Herein we present the case of a 77-year-old woman with a history of treated diffuse large B-cell lymphoma who presented with neurological symptoms four months after she was declared to be in remission. Her initial head computed tomography scan showed multiple low-attenuated lesions in her brain and a contrast enhanced magnetic resonance imaging scan showed multiple T1- and T2- enhancing lesions in the basal ganglia and at the gray-white junction. The clinical team was highly suspicious of a recurrence of her lymphoma so she had an extensive workup, including a brain biopsy, which did not lead to a definite diagnosis. After she died, an autopsy was performed, and multiple necrotic lesions were discovered in her brain. Histologic sections demonstrated numerous parasitic organisms, and immunohistochemical staining for Toxoplasma gondii was positive, confirming the diagnosis of cerebral toxoplasmosis. This case highlights an unusual case of cerebral toxoplasmosis that was diagnosed at autopsy and reviews the relevant radiographic findings as well as the gross and microscopic pathological features of the disease.